Social Network Theory, Sigma Six, and Customer Experience Management: Common Elements that Aid Positive Sales-marketing Interface: A Review of the Literature - Mgiba, Freddy Marilahimbilu (International Review of Management and Marketing, 2019)
In conventional organizational structures, Sales and Marketing are two of the most crucial divisions that interact both directly and indirectly with customers, and with each other. Together, they have an impact on marketing intelligence gathering, customer perceptions of organizations, and ultimately on organizational performance outcomes. However, the quality of their interactions and how they are coordinated internally have often been found wanting in many instances. To aid the understanding of ideal interactions between these functions, different theories were used in isolation, which in turn limited their theoretical explanatory power and management usefulness. The present article attempts to build a case for a proper intergration and possible changes to the traditional structure of the Sales and Marketing functions by use of the Social network, Customer experience, and Sigma six theories. Synergistically combining these theories exponentially extends their explanatory powers and provides the rationale for a combination of these functions. Toward that end, literature was reviewed on the Sales and marketing divisions and the three theories, a concept matrix clearly showing the link between the two functions and the three theories was designed, a string of propositions was given, and a research framework was proposed. The benefits to academia are that new research directions for organizational structure in the light of efficiency requirements are provided. The propositions also have potential practical applications for conflict management as the proposals necessitates a rethink of the interface between these two functions, and that would also eliminate turf wars. Keywords: Theories, structure, perceptions, actions, performance, outcomes, marketing intelligence JEL Classifications: M31, M39 DOI: https://doi.org/10.32479/irmm.8674